Association between inflammatory obesity phenotypes, FTO-rs9939609, and cardiovascular risk factors in patients with type 2 diabetes - Meysam Alipour; Hosein Rostami; Karim Parastouei (Journal of Research in Medical Sciences, 2020)
Background: The role of inflammatory states in cardiometabolic risks among patients with type 2 diabetes mellitus (T2DM) with similar degrees of obesity is unknown. The study aimed to compare cardiometabolic risk factors in inflammatory obesity phenotypes with regard to the role of the FTO rs9939609 gene polymorphism. Materials and Methods: This study was performed on 155 patients with T2DM (77 men and 78 women) in Ahvaz, Iran. Participants were grouped into four groups based on the presence of obesity and inflammation (high-sensitivity C-reactive protein ≥3.9 mg/L): low inflammatory normal weight (LINW), high inflammatory normal weight (HINW), low inflammatory obese (LIO), and high inflammatory obese (HIO). The genotypes of FTO rs9939609, including homozygous carriers of the FTO risk allele (AA), heterozygous carriers (AT), and carrying no risk allele (TT), were studied. The cardiometabolic risk factors, including anthropometric status, hypertension, lipid and glycemic profile, and inflammatory markers, were evaluated. The waist–hip ratio (WHR), mean arterial pressure (MAP), and atherogenic index of plasma (AIP) were calculated. Results: The patients in inflammatory groups (HINW and HIO) have significantly higher levels in AIP when compared to inflammatory healthy groups (LINW and LIO). No significant differences between any of the four group means were detected in WHR, blood pressure, MAP, glycemic status (fasting blood sugar and insulin), homeostatic model assessment, lipid profile (triglyceride, very low-density lipoprotein, high-density lipoprotein, low-density lipoprotein, and cholesterol), interleukin-6, and total antioxidant capacity. The most frequent of high-risk genotype (AA) of FTO rs9939609 was in HIO, LIO, HINW, and LINW. Conclusion: T2DM patients with inflammatory condition have similar degree of increased atherogenic risk irrespective of obesity. The obesity-risk genotype AA of FTO gene was associated with an increased risk for inflammatory obesity in T2DM patients.